Influences of Seasons, Latitudes, and Host Plants on Metabolic Changes in Cuscuta campestris Yunck - 유찬우 (The Graduate School, Ajou University, 2024)
To determine whether the metabolomic patterns of Cuscuta campestris vary with_x000D_ season and latitude, samples were collected from parasitized individuals on the same_x000D_ host plant. In order to include any potential metabolomic difference resulting from_x000D_ host plant, the host plants were restricted to two species: Humulus japonicus and_x000D_ Artemisia sp. Metabolite profiles of C. campestris were analyzed by different seasons_x000D_ and latitudes conditions using gas chromatography-mass spectrometry (GC-MS)._x000D_ Principal component analysis (PCA) was conducted to examine the metabolite_x000D_ patterns and the PCA score plots of entire samples showed genetic influences more_x000D_ than environmental influences: seasons and latitudes. When looking at the metabolite_x000D_ patterns of C. campestris across the entire sample set, low latitude samples appear to_x000D_ be relatively distinct from high and middle latitude samples. For samples with H._x000D_ japonicus as the host plant, the metabolite pattern showed a clear distinction between_x000D_ the middle latitude group and the other groups. these patterns did not show the_x000D_ expected high-middle-low order. On the other hand, samples with Artemisia sp. as the_x000D_ host plant, they tended to be well distinction among season and latitude groups_x000D_ mainly when October samples were included._x000D_ Multivariate analysis of variance (MANOVA) was used to interpret whether_x000D_ statistically significant differences between the groups. The whole plant-seed group_x000D_ was significant in all comparison. In the season groups using PCA scores, high_x000D_ significances were observed only when compared to October, while comparisons_x000D_ between other seasons were less significant or not significant. In the latitude groups,_x000D_ the significant differences between groups were varied with each comparison._x000D_ This study provides clues to understand the changes in metabolites of C._x000D_ campestris from an ecological perspective. The limitations of this study included the_x000D_ absence of Artemisia sp. related samples collected in the October season, the inability_x000D_ to analyze the difference between the host plant with and without parasitism, and the_x000D_ absence of environmental data.
학위논문(석사)--생명과학과,2024. 8
Keywords: Cuscuta campestris; GC-MS; latitude; metabolite profile; parasitic plant; season; seed